Digging for letters. (2nd May 2019) - Harries, Judith
Abstract : In the final part of this series on sand play, Judith Harries focuses on sand as a fantastic resource for exploring letters of the alphabet, using magnetic letters, pebbles, vehicles and cardboard tubes.